(untitled) (Archive of Conferences, 2020)
This article argues that in Uzbekistan, the development of the educational sphere is considered at the level of state policy, primarily comprehensive support for young people seeking to master modern science. It is necessary to note the current territory of Uzbekistan went down in history as an ancient cradle of science, culture and art and the first Renaissance period in the IX-XII centuries and the second Renaissance period in the XIV-XVI centuries as the habitat of great scientists and thinkers who made a great contribution to the development of world science. It should be noted that the spirit and blood of our great ancestors still exist in our youth, and therefore they will become the founder of the third Renaissance